1988
DOI: 10.1002/jnr.490200305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GD3 ganglioside by developing rat cerebellar purkinje cells in situ

Abstract: GD3 is a major ganglioside of the immature vertebrate CNS, and its expression is suggested to be characteristic of immature neuroectodermal cells. Using immunocytochemistry on cryostat sections of developing rat cerebellum with a monoclonal antibody specific for GD3, we have found that GD3 begins to be expressed on the plasma membrane of Purkinje cell bodies and dendrites beginning at postnatal day 7. Staining became brighter as the dendritic tree of the cells enlarged. As the Purkinje cells began to mature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In the PL, we found anti-GD3 staining in the cytoplasm of the Purkinje cell bodies. Although previously regarded mainly as a marker of astrocytes, microglia and neuroectodermal cells (Goldman and Reynolds, 1996), ganglioside GD3 expression in Purkinje cells has also been reported previously (Reynolds and Wilkin, 1988;Kawai et al, 1994;Yamamoto et al, 1994). Kotani et al (1995) reported no anti-GD3 staining in the PL.…”
Section: Discussionmentioning
confidence: 86%
“…In the PL, we found anti-GD3 staining in the cytoplasm of the Purkinje cell bodies. Although previously regarded mainly as a marker of astrocytes, microglia and neuroectodermal cells (Goldman and Reynolds, 1996), ganglioside GD3 expression in Purkinje cells has also been reported previously (Reynolds and Wilkin, 1988;Kawai et al, 1994;Yamamoto et al, 1994). Kotani et al (1995) reported no anti-GD3 staining in the PL.…”
Section: Discussionmentioning
confidence: 86%
“…It has been suggested that gangliosides become antigenic only after acetone treatment, because acetone may act to promote the accessibility of the ganglioside (Graus et al 1994) or may unmask membrane-bound carbohydrates (Thorpe and Kerr 1994). However, no GM3 was detected with an anti-GM3 antibody in prefixed cryostat sections after acetone treatment (Daniotti et al 1994) or after tratment of formaldehyde-fixed tissue sections with methanol, acetone, or ethanol/acetic acid (Reynolds and Wilkin 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, using two different antibodies to ganglioside GD3, opposite conclusions were reached about the presence of GD3 in rat cerebellar Purkinje cells. With monoclonal antibody (MAb) R24 no labeling of Purkinje cells was observed (Goldman et al 1984), but labeling was observed with the LB1 antibody (Reynolds and Wilkin 1988). Although these differences could be caused by each antibody recognizing different epitopes on ganglioside GD3, a more likely explanation is that the different fixation methods used in each study (Reynolds and Wilkin 1988) are responsible for the different results.…”
mentioning
confidence: 99%
“…However, this reactivity is lost as the cells begin to migrate through the molecular layer. In a study of LB1 binding in the developing cerebellum Purkinje cells were found to express GD3 in the cell membranes of the dendritic tree (Reynolds and Wilkin, 1988b). GD3+ Purkinje cells were first seen at 7 days postnatal and a n increase in the intensity of the immunostaining was observed as the dendritic tree increased in complexity, correlating well with climbing fibre synaptogenesis.…”
Section: G3expression By Neuronal Subpopulationsmentioning
confidence: 97%